EFEK BEBAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT TELKOM AKSES WITEL BANTEN BARAT - Ratna Sari, Rosmida; Fatari, Fatari; Fauji, Ade (Yayasan Education and Social Center, 2024)
The aim of this research is to determine the effect of workload and work stress on turnover intention through work motivation as an intervening variable at PT. Telkom Access Witel West Banten. This research uses a quantitative approach. The sampling technique was the proportionate stratified random sampling method with a population of 274 using the Slovin formula resulting in a sample of 73 respondents. The results of calculating the direct effect of workload on turnover intention have no effect based on a t-statistic value of 0.103 and a p-value of 0.918. The direct effect of work stress on employee turnover intention has no effect based on a t-statistic value of 0.456 and a p-value of 0.648. The direct effect of work motivation on turnover intention is based on a t-statistic value of 3.880 and a p-value of 0.000. The direct effect of workload on work motivation has no effect based on a t-statistic value of 0.083 and a p-value of 0.934. The direct effect of work stress on work motivation is based on a t-statistic value of 2.824 and a p-value of 0.005. The indirect effect of workload through work motivation as an intervening variable on turnover intention, has an effect based on a t-statistic value of 0.079 and a p-value of 0.937. The indirect effect of work stress through work motivation as an intervening variable on turnover intention, based on a t-statistic value of 1.758 and a p-value of 0.079. It can be concluded that work motivation on turnover intention has a positive and significant effect. And work stress on work motivation has a positive and significant effect.